Absorbable hemostatic powder and preparation method thereof

The starch/cyclodextrin composite microspheres were prepared by modifying potato starch and hydroxypropyl-β-cyclodextrin composite microspheres, which solved the problem of insufficient water absorption and viscosity of existing hemostatic materials, and achieved efficient hemostatic effect and safe degradation performance.

CN119770705APending Publication Date: 2025-04-08QINGDAO ZHONGTENG BIOTECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510037042.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing absorbable hemostatic materials have problems such as tissue necrosis, allergic reactions, stimulation reactions and local adhesions when used, and the water absorption rate of ordinary starch materials and the viscosity after water absorption are insufficient, which affects the hemostatic effect.

Method used

Modified potato starch is combined with hydroxypropyl-β-cyclodextrin, and starch/cyclodextrin composite microspheres are prepared through gelatinization, emulsification and crosslinking, which improves their specific surface area and porous structure, thereby enhancing water absorption and viscosity.

Benefits of technology

The water absorption capacity of modified potato starch and the viscosity after absorption are improved, the blood is absorbed quickly, the coagulation mechanism is triggered, and the rapid hemostasis is achieved, and the degradation in the human body is avoided, and allergic reactions and tissue necrosis are avoided.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present application relates to the field of medical hemostatic powder, and specifically discloses an absorbable hemostatic powder and a preparation method thereof. A preparation method of an absorbable hemostatic powder comprises the following steps: S1: adding modified potato starch and hydroxypropyl-β-cyclodextrin to water, gelatinizing at 50-55°C to obtain a homogeneous solution; S2: adding a cross-linking agent to the homogeneous solution, mixing evenly, dropping it into liquid paraffin containing an emulsifier, emulsifying at 55-60°C for 30-40min to obtain an emulsion; S3: adding sodium bisulfite to the emulsion, stirring at 350-380r / min for 2-3h, centrifuging and washing for multiple times to obtain starch / cyclodextrin composite microspheres, i.e., absorbable hemostatic powder; in addition, the preparation method of the present application has the advantage of improving the hemostatic effect of the hemostatic powder.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of medical hemostatic powder, and more specifically, to an absorbable hemostatic powder and a preparation method thereof. Background Art

[0002] With the improvement of people's living standards and medical conditions, the quality requirements for the commonly used medical method - surgery are also rising. As hemostasis is an important part of clinical treatment, it can be foreseen that the application of hemostatic materials will become more and more extensive. At present, the main absorbable hemostatic materials used at home and abroad are fibrin glue, oxidized cellulose and oxidized regenerated cellulose, α-cyanoacrylate tissue glue, chitosan, etc.

[0003] However, there are still some problems when using common absorbable hemostatic materials, such as tissue necrosis caused by zeolite, oxidized regenerated cellulose, etc.; allergic reactions induced by collagen, non-human thrombin, etc.; irritation caused by cyanoacrylate tissue glue, glutaraldehyde-albumin, etc.; local adhesion formed by gelatin, cellulose ethers, etc. Starch products have the advantages of complete absorption, no residue, and no animal protein. They are safe, non-toxic and have good adsorption capacity. They can play a hemostatic role by inducing platelet aggregation, promoting thrombosis and activating the coagulation system. It is an ideal hemostatic material. However, the water absorption rate and viscosity of ordinary starch materials after water absorption need to be improved. When used, they are prone to insufficient water absorption and insufficient viscosity, which affects the hemostatic effect of the hemostatic material. Summary of the invention

[0004] In order to improve the hemostatic effect of hemostatic powder, the present application provides an absorbable hemostatic powder and a preparation method thereof.

[0005] In a first aspect, the present application provides a method for preparing absorbable hemostatic powder, using the following technical solution: A method for preparing absorbable hemostatic powder comprises the following steps: S1: adding modified potato starch and hydroxypropyl-β-cyclodextrin into water and gelatinizing at 50-55°C to prepare a homogeneous solution; S2: adding a crosslinking agent to the homogeneous solution, mixing evenly, and then dropping it into liquid paraffin containing an emulsifier, and emulsifying at 55-60° C. for 30-40 minutes to obtain an emulsion; S3: Add sodium bisulfite to the emulsion, stir at 350-380 r / min for 2-3 hours, wash by centrifugation for multiple times, and freeze-dry to obtain starch / cyclodextrin composite microspheres, which are absorbable hemostatic powder.

[0006] By adopting the above technical scheme, the modified potato starch has a strong water absorption capacity, the microspheres have a large specific surface area and adsorption capacity, and can effectively improve the water absorption capacity of the modified potato starch. The modified potato starch is compounded with hydroxypropyl-β-cyclodextrin, which can effectively improve the specific surface area and porous structure of the starch / cyclodextrin composite microspheres. The starch / cyclodextrin composite microspheres can quickly absorb water after contacting the blood, thereby increasing the concentration of coagulation factors such as platelets in the blood, triggering the coagulation mechanism, and thus achieving the effect of rapid hemostasis. At the same time, the starch / cyclodextrin composite microspheres can be degraded in the human body, do not contain animal protein, are not likely to cause allergic reactions, and the degradation products are harmless to the human body and are not likely to cause necrosis of human tissues.

[0007] The addition of hydroxypropyl-β-cyclodextrin can increase the viscosity of the starch / cyclodextrin composite microspheres after absorbing water, so that the absorbable hemostatic powder can quickly absorb blood after use, forming a sticky covering near the wound to seal the wound and reduce blood outflow. At the same time, the covering has good viscosity and is not easily dispersed by blood, which makes the absorbable hemostatic powder have a good hemostatic effect.

[0008] Preferably, the mass ratio of the modified potato starch to hydroxypropyl-β-cyclodextrin is (2.13-2.54):(0.73-0.82).

[0009] By adopting the above technical scheme and controlling the mass ratio of modified potato starch to hydroxypropyl-β-cyclodextrin, the starch / cyclodextrin composite microspheres have a better morphology, the microstructure of the microspheres is neatly arranged, and they have a higher specific surface area and water absorption.

[0010] Preferably, the preparation method of the modified potato starch comprises the following steps: dissolving potato starch in water, stirring with magnetic force to form a suspension, adding a composite enzyme, performing enzymolysis at 45-50° C. for 12 hours, adding a sodium hydroxide solution, centrifuging, washing, and drying to obtain enzymolyzed potato starch; After dispersing enzymatically hydrolyzed potato starch in water to obtain a suspension, deacetylated konjac glucomannan is added, stirred and mixed evenly at 30-35° C., centrifuged, and dried to obtain modified potato starch.

[0011] By adopting the above technical scheme, after the potato starch is enzymatically hydrolyzed by the composite enzyme, the surface of the potato starch is eroded, and more uneven concave and convex surfaces appear, which increases the porosity of the potato starch, thereby improving the water absorption of the enzymatically hydrolyzed potato starch; the deacetylated konjac glucomannan has good water absorption, and after being mixed with the enzymatically hydrolyzed potato starch, it can improve the water absorption of the modified potato starch and the viscosity after water absorption, thereby improving the hemostatic effect of the absorbable hemostatic powder.

[0012] Preferably, the complex enzyme comprises maltotriosidase and α-amylase in a mass ratio of (0.92-1.12):(6.81-7.21), and the added amount of the complex enzyme is 7.5-8.3wt% of the mass of potato starch.

[0013] By adopting the above technical scheme, maltotriase and α-amylase are used in combination, which has a better enzymatic hydrolysis effect on potato starch. By controlling the mass ratio of the two and the addition amount of the composite enzyme, the surface of the enzymatically hydrolyzed potato starch can have more concave and convex pores, and at the same time, the porous structure will not collapse due to excessive enzymatic hydrolysis, which is beneficial to improving the water absorption of the enzymatically hydrolyzed potato starch.

[0014] Preferably, the mass ratio of the deacetylated konjac glucomannan to the enzymatically hydrolyzed potato starch is (0.83-0.91):(7.26-8.13).

[0015] By adopting the above technical scheme, the mass ratio of deacetylated konjac glucomannan to enzymatically hydrolyzed potato starch is controlled, so that the absorbable hemostatic powder has good viscoelasticity and water retention after absorbing water. If the amount of deacetylated konjac glucomannan added is too much, the network structure formed by the absorbable hemostatic powder after absorbing water is too dense, the hardness is increased, and it is easy to break, thereby affecting the recovery of the wound.

[0016] Preferably, the deacetylation degree of the deacetylated konjac glucomannan is 45.62-51.91%.

[0017] By adopting the above technical scheme, the deacetylation degree of deacetylated konjac glucomannan affects the enhancement of the viscosity of absorbable hemostatic powder by deacetylated konjac glucomannan. Too high or too low deacetylation degree will reduce the water absorption and viscosity of modified potato starch after water absorption.

[0018] Preferably, the hydroxypropyl-β-cyclodextrin is treated as follows: adding hydroxypropyl-β-cyclodextrin to a sodium carbonate solution, stirring until completely swollen, adding chitosan, stirring and refluxing at 85-90° C. for 2-2.5 hours, adjusting the pH to neutral, filtering, washing, and drying.

[0019] By adopting the above technical scheme, after hydroxypropyl-β-cyclodextrin is treated, the surface of hydroxypropyl-β-cyclodextrin is modified by chitosan, the specific surface area is increased, and the water absorption is good, which is beneficial to improve the water absorption of starch / cyclodextrin composite microspheres, thereby improving the hemostatic effect of the absorbable hemostatic powder.

[0020] Preferably, the starch / cyclodextrin composite microspheres are further treated as follows: the starch / cyclodextrin composite microspheres are dispersed in a 2-4wt% sodium alginate solution, placed in a 55-60°C water bath, stirred for reaction for 6-7h, then calcium chloride solution is added dropwise, and after the addition is complete, the stirring reaction is continued for 20-30min, soaked for 4-5h, centrifuged, washed, and freeze-dried.

[0021] By adopting the above technical scheme, the starch / cyclodextrin composite microspheres are immersed in a sodium alginate solution, so that the surface of the starch / cyclodextrin composite microspheres is coated with a layer of sodium alginate. After calcium chloride is dropped, the calcium ions are cross-linked with the sodium alginate, and ion exchange is performed to form calcium alginate. Calcium alginate can promote red blood cell aggregation, accelerate the coagulation process, and further improve the hemostasis speed.

[0022] Preferably, the mass ratio of calcium chloride to sodium alginate is (0.85-0.96):(0.91-1.02).

[0023] By adopting the above technical solution and controlling the mass ratio of calcium chloride and sodium alginate, the generation of calcium alginate can be effectively controlled, so that calcium alginate has good viscosity and water absorption, and can effectively promote the coagulation process.

[0024] In a second aspect, the present application provides an absorbable hemostatic powder, which adopts the following technical solution: The invention discloses an absorbable hemostatic powder, which is prepared according to a preparation method of the absorbable hemostatic powder.

[0025] By adopting the above technical scheme, the absorbable hemostatic powder prepared according to the preparation method of the present application has good water absorption, has high viscoelasticity after absorbing water, and can be degraded and absorbed in the human body, and has a good hemostatic effect.

[0026] In summary, this application has the following beneficial effects: 1. In the present application, the modified potato starch has a strong water absorption capacity, and the microspheres have a large specific surface area and adsorption capacity, which can effectively improve the water absorption capacity of the modified potato starch. The modified potato starch is compounded with hydroxypropyl-β-cyclodextrin, which can effectively improve the specific surface area and porous structure of the starch / cyclodextrin composite microspheres. The starch / cyclodextrin composite microspheres can quickly absorb water after contacting the blood, thereby increasing the concentration of coagulation factors such as platelets in the blood, triggering the coagulation mechanism, and thus achieving the effect of rapid hemostasis. At the same time, the starch / cyclodextrin composite microspheres can be degraded in the human body, do not contain animal protein, are not easy to cause allergic reactions, and the degradation products are harmless to the human body and are not easy to cause necrosis of human tissues.

[0027] 2. In the present application, by controlling the mass ratio of modified potato starch to hydroxypropyl-β-cyclodextrin, the morphology of starch / cyclodextrin composite microspheres is improved, the microstructure of the microspheres is neatly arranged, and they have a higher specific surface area and water absorption.

[0028] 3. In the present application, after the potato starch is hydrolyzed by the composite enzyme, the surface of the potato starch is eroded, and more uneven concave and convex surfaces appear, which increases the porosity of the potato starch, thereby improving the water absorption of the enzymatically hydrolyzed potato starch; deacetylated konjac glucomannan has good water absorption. After mixing with the enzymatically hydrolyzed potato starch, it can improve the water absorption and viscosity of the modified potato starch after water absorption, thereby improving the hemostatic effect of the absorbable hemostatic powder. DETAILED DESCRIPTION

[0029] The present application is further described in detail below with reference to the embodiments.

[0030] Preparation Example 1-10 of Modified Potato Starch Preparation Example 1 3.2 g of potato starch was dissolved in 40 mL of water, and after being uniformly stirred by magnetic force to form a suspension, a composite enzyme was added, and after enzymatic hydrolysis at 45° C. for 12 h, 3 mL of 4 wt % sodium hydroxide solution was added, and the mixture was centrifuged, washed, and dried to obtain enzymatically hydrolyzed potato starch, wherein the composite enzyme included maltotriosidase and α-amylase in a mass ratio of 0.92:6.81, and the amount of the composite enzyme added was 7.5 wt % of the mass of the potato starch; After dispersing 6.8 g of enzymatically hydrolyzed potato starch in 95 mL of water to prepare a suspension, deacetylated konjac glucomannan was added, the mass ratio of deacetylated konjac glucomannan to enzymatically hydrolyzed potato starch was 0.83:7.26, and the deacetylation degree of deacetylated konjac glucomannan was 45.62%. After stirring and mixing at 30° C., the mixture was centrifuged and dried to prepare modified potato starch.

[0031] Preparation Example 2 2.9 g of potato starch was dissolved in 45 mL of water, and after being uniformly stirred by magnetic force to form a suspension, a composite enzyme was added, and after enzymatic hydrolysis at 50° C. for 12 h, 4 mL of 4 wt % sodium hydroxide solution was added, and the mixture was centrifuged, washed, and dried to obtain enzymatically hydrolyzed potato starch, wherein the composite enzyme included maltotriosidase and α-amylase in a mass ratio of 1.12:9.21, and the amount of the composite enzyme added was 8.3 wt % of the mass of the potato starch; After dispersing 7.5 g of enzymatically hydrolyzed potato starch in 100 mL of water to prepare a suspension, deacetylated konjac glucomannan was added, the mass ratio of deacetylated konjac glucomannan to enzymatically hydrolyzed potato starch was 0.91:8.13, the deacetylation degree of deacetylated konjac glucomannan was 51.91%, and the mixture was stirred and mixed uniformly at 35° C., centrifuged, and dried to prepare modified potato starch.

[0032] Preparation Example 3 The difference between Preparation Example 3 and Preparation Example 1 is that in Preparation Example 3, the composite enzyme includes maltotriosidase and α-amylase in a mass ratio of 0.92:4.21.

[0033] Preparation Example 4 The difference between Preparation Example 4 and Preparation Example 1 is that in Preparation Example 4, the composite enzyme includes maltotriosidase and α-amylase in a mass ratio of 0.92:10.21.

[0034] Preparation Example 5 The difference between Preparation Example 5 and Preparation Example 1 is that in Preparation Example 5, the added amount of the complex enzyme is 5.5wt% of the mass of potato starch.

[0035] Preparation Example 6 The difference between Preparation Example 6 and Preparation Example 1 is that in Preparation Example 6, the added amount of the complex enzyme is 10.8wt% of the mass of potato starch.

[0036] Preparation Example 7 The difference between Preparation Example 7 and Preparation Example 1 is that in Preparation Example 7, the mass ratio of deacetylated konjac glucomannan to enzymatically hydrolyzed potato starch is 0.83:5.18.

[0037] Preparation Example 8 The difference between Preparation Example 8 and Preparation Example 1 is that in Preparation Example 8, the mass ratio of deacetylated konjac glucomannan to enzymatically hydrolyzed potato starch is 0.83:11.67.

[0038] Preparation Example 9 The difference between Preparation Example 9 and Preparation Example 1 is that in Preparation Example 9, the deacetylation degree of the deacetylated konjac glucomannan is 32.68%.

[0039] Preparation Example 10 The difference between Preparation Example 10 and Preparation Example 1 is that in Preparation Example 10, the deacetylation degree of the deacetylated konjac glucomannan is 75.91%. Example

[0040] Example 1 A method for preparing absorbable hemostatic powder comprises the following steps: S1: 2.5 g of modified potato starch and hydroxypropyl-β-cyclodextrin were added to 35 mL of water, the mass ratio of modified potato starch to hydroxypropyl-β-cyclodextrin was 2.13:0.73, and gelatinization was performed at 50° C. to obtain a homogeneous solution. The modified potato starch was the modified potato starch obtained in Preparation Example 1; S2: Add 0.3 g of sodium trimetaphosphate to the homogeneous solution, mix well, and then add dropwise to 70 mL of liquid paraffin containing 0.8 g of Span-80 and 0.25 g of Tween-80, and emulsify at 60° C. for 30 min to obtain an emulsion; S3: Add 0.6 g of sodium bisulfite to the emulsion, stir at 380 r / min for 2 h, wash by centrifugation for multiple times, and freeze-dry to obtain starch / cyclodextrin composite microspheres, which are absorbable hemostatic powder.

[0041] Example 2 A method for preparing absorbable hemostatic powder comprises the following steps: S1: 2.5 g of modified potato starch and hydroxypropyl-β-cyclodextrin were added to 30 mL of water, the mass ratio of modified potato starch to hydroxypropyl-β-cyclodextrin was 2.54:0.82, and gelatinization was performed at 55° C. to obtain a homogeneous solution. The modified potato starch was selected from the modified potato starch prepared in Preparation Example 2; S2: Add 0.5 g of sodium trimetaphosphate to the homogeneous solution, mix well, and then dropwise add to 80 mL of liquid paraffin containing 0.9 g of Span-80 and 0.35 g of Tween-80, and emulsify at 55° C. for 40 min to obtain an emulsion; S3: Add 0.5 g of sodium bisulfite to the emulsion, stir at 350 r / min for 3 h, wash by centrifugation for multiple times, and freeze-dry to obtain starch / cyclodextrin composite microspheres, which are absorbable hemostatic powder.

[0042] Example 3 The difference between Example 3 and Example 1 is that in Example 3, the modified potato starch is the modified potato starch prepared in Preparation Example 3.

[0043] Example 4 The difference between Example 4 and Example 1 is that in Example 4, the modified potato starch is the modified potato starch prepared in Preparation Example 4.

[0044] Example 5 The difference between Example 5 and Example 1 is that in Example 5, the modified potato starch is the modified potato starch prepared in Preparation Example 5.

[0045] Example 6 The difference between Example 6 and Example 1 is that in Example 6, the modified potato starch is the modified potato starch prepared in Preparation Example 6.

[0046] Example 7 The difference between Example 7 and Example 1 is that in Example 7, the modified potato starch is the modified potato starch prepared in Preparation Example 7.

[0047] Example 8 The difference between Example 8 and Example 1 is that in Example 8, the modified potato starch is the modified potato starch prepared in Preparation Example 8.

[0048] Example 9 The difference between Example 9 and Example 1 is that in Example 8, the modified potato starch is the modified potato starch prepared in Preparation Example 9.

[0049] Example 10 The difference between Example 10 and Example 1 is that in Example 10, the modified potato starch is the modified potato starch prepared in Preparation Example 10.

[0050] Embodiment 11 The difference between Example 11 and Example 1 is that in Example 11, the mass ratio of modified potato starch to hydroxypropyl-β-cyclodextrin is 2.13:0.25.

[0051] Example 12 The difference between Example 12 and Example 1 is that in Example 12, the mass ratio of modified potato starch to hydroxypropyl-β-cyclodextrin is 2.13:1.23.

[0052] Embodiment 13 The difference between Example 13 and Example 1 is that in Example 13, hydroxypropyl-β-cyclodextrin is treated as follows: 3.12 g of hydroxypropyl-β-cyclodextrin is added to 30 mL of 10 wt% sodium carbonate solution, stirred until completely swollen, 0.35 g of chitosan is added, stirred and refluxed at 85°C for 2.5 h, the pH is adjusted to neutral, and then filtered, washed, and dried.

[0053] Embodiment 14 The difference between Example 14 and Example 1 is that in Example 14, hydroxypropyl-β-cyclodextrin is treated as follows: 2.55 g of hydroxypropyl-β-cyclodextrin is added to 35 mL of 12 wt% sodium carbonate solution, stirred until completely swollen, 0.4 g of chitosan is added, stirred and refluxed at 90°C for 2 h, the pH is adjusted to neutral, and then filtered, washed, and dried.

[0054] Embodiment 15 The difference between Example 15 and Example 1 is that in Example 15, the starch / cyclodextrin composite microspheres are further treated as follows: 2.1 g of starch / cyclodextrin composite microspheres are dispersed in 15 mL of 2 wt% sodium alginate solution, placed in a 55°C water bath, stirred for reaction for 3 hours, and then 6 wt% calcium chloride solution is added dropwise, with a mass ratio of calcium chloride to sodium alginate of 0.85:0.91. After the addition is completed, the stirring reaction is continued for 20 minutes, soaked for 5 hours, centrifuged, washed, and freeze-dried.

[0055] Example 16 The difference between Example 16 and Example 1 is that in Example 16, the starch / cyclodextrin composite microspheres are further treated as follows: 2.3 g of starch / cyclodextrin composite microspheres are dispersed in 17 mL of 4 wt% sodium alginate solution, placed in a 60°C water bath, stirred for reaction for 4 hours, and then 8 wt% calcium chloride solution is added dropwise, with a mass ratio of calcium chloride to sodium alginate of 0.96:1.02. After the addition is completed, the stirring reaction is continued for 30 minutes, soaked for 4 hours, centrifuged, washed, and freeze-dried.

[0056] Embodiment 17 The difference between Example 17 and Example 15 is that in Example 17, the mass ratio of calcium chloride to sodium alginate is 0.85:0.52.

[0057] Embodiment 18 The difference between Example 18 and Example 15 is that in Example 18, the mass ratio of calcium chloride to sodium alginate is 0.85:1.46.

[0058] Comparative Example Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that in Comparative Example 1, an equal amount of potato starch is used to replace the modified potato starch.

[0059] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that in Comparative Example 2, hydroxypropyl-β-cyclodextrin is not added, that is, the homogeneous solution does not contain hydroxypropyl-β-cyclodextrin, and the modified potato starch microspheres obtained are absorbable hemostatic powder.

[0060] Test methods According to the preparation methods of Examples 1-14 and Comparative Examples 1-2, absorbable hemostatic powder was obtained, and the water absorption rate, hemostatic effect and viscosity after water absorption of the absorbable hemostatic powder were tested, and the results were recorded in Table 1. The test method is as follows: Water absorption rate: Weigh a certain mass of hemostatic powder, record it as m 1 , add it to 20℃ distilled water, stir it slightly, soak it for 40 minutes to fully absorb water, then filter it with a vacuum filter to drain the water, weigh it, and record it as m 2 Calculate the water absorption rate according to the following formula: Water absorption rate = (m 2 -m 1 ) / m 1 ×100% Hemostatic effect: All surgical instruments and equipment were sterilized and dried before surgery, and ultraviolet disinfection was performed for more than 30 minutes before use in the operating room. 16 rats were weighed and anesthetized with 3% sodium pentobarbital solution through the ear vein under sterile conditions. The anesthesia dosage was 1.2 mL / kg. The rats were fixed on the operating table in the supine position. The abdomen was routinely prepared, disinfected, and draped. The abdominal wall was cut in the middle to enter the abdominal cavity. The same animal was excised from the surface of the liver and spleen. 1cm×1cm×0.1cm tissue blocks were formed on the surface of the liver and spleen to form bleeding and bleeding wounds. The wounds were covered with hemostatic powders of each group, and the middle finger was slightly pressed to make the absorbable hemostatic powder close to the wound surface. The bleeding time was recorded by the same tail-cutting method for mice. The hemostatic sample was directly pressed on the bleeding wound. The amount of absorbable hemostatic powder was adjusted according to the hemostasis of the wound. The surface was covered with sterile gauze for compression and hemostasis. The hemostasis time and sample volume were recorded.

[0061] Viscosity: After 1g of absorbable hemostatic powder is added with water until it is saturated with water to form a gel-like object, its viscosity work index is measured using a texture analyzer. The test probe is: P36R (cylindrical probe), the test conditions are room temperature, speed before test: 0.5mm / s; test speed: 1mm / s; speed after test: 10mm / s; stress 100g; recovery distance 5.0mm; contact time: 10s; trigger type: automatic-5g, record viscosity work.

[0062] Table 1 Performance test of absorbable hemostatic powder project Water absorption / % Hemostasis time / s Sample amount / g Viscous work / (g·mm) Example 1 3208 45 0.10 358 Example 2 3267 43 0.11 346 Example 3 2819 68 0.16 298 Example 4 2764 72 0.18 324 Example 5 2591 71 0.20 326 Example 6 2846 69 0.19 306 Example 7 2651 83 0.18 349 Example 8 2419 61 0.21 286 Example 9 2913 86 0.17 334 Example 10 2674 79 0.19 336 Embodiment 11 2914 83 0.17 327 Example 12 2591 68 0.20 302 Embodiment 13 3398 34 0.05 413 Embodiment 14 3462 32 0.06 419 Embodiment 15 3406 32 0.06 412 Example 16 3437 31 0.07 423 Embodiment 17 3257 38 0.09 384 Embodiment 18 3398 33 0.07 408 Comparative Example 1 1659 112 0.25 49 Comparative Example 2 1735 109 0.23 57 According to Examples 1-2, Table 1 and Comparative Examples 1-2, it can be seen that the absorbable hemostatic powder prepared in Examples 1-2 has good water absorption, good viscosity after absorbing water, and a shorter hemostatic time is achieved using a smaller sample amount, indicating that the absorbable hemostatic powder prepared in Examples 1-2 has a good hemostatic effect. The absorbable hemostatic powder is a starch / cyclodextrin composite microsphere, which is a microsphere formed by cross-linking modified potato starch and hydroxypropyl-β-cyclodextrin. The potato starch is enzymatically hydrolyzed and blended to obtain a modified potato starch, which has a strong water absorption capacity. After the modified potato starch is cross-linked with hydroxypropyl-β-cyclodextrin to form microspheres, the starch The powder / cyclodextrin composite microspheres have a large specific surface area and adsorption capacity, which effectively improves the water absorption capacity of the absorbable hemostatic powder. After the modified potato starch is compounded with hydroxypropyl-β-cyclodextrin, the specific surface area and porous structure of the starch / cyclodextrin composite microspheres can be effectively improved, thereby improving the water absorption capacity of the starch / cyclodextrin composite microspheres. After the absorbable hemostatic powder contacts the wound, it quickly absorbs blood, causing the coagulation factors in the blood to be enriched and the concentration to increase, thereby triggering the coagulation mechanism and achieving the effect of rapid hemostasis. At the same time, the absorbable hemostatic powder has good viscosity after absorbing water, can cover the wound and play a bonding role, and reduce blood outflow.

[0063] Comparative Example 1 uses potato starch instead of modified potato starch. The water absorption rate and viscosity of the absorbable hemostatic powder prepared in Comparative Example 1 are reduced when used, and the hemostatic time and sample usage are increased during hemostasis, indicating that the hemostatic effect of the absorbable hemostatic powder prepared in Comparative Example 1 is inferior to that of Example 1. The water absorption capacity of potato starch is lower than that of modified potato starch, so that the water absorption capacity of the prepared starch / cyclodextrin composite microspheres is lower than that of the starch / cyclodextrin composite microspheres prepared in Example 1, and the viscosity after water absorption is also reduced, so that when the absorbable hemostatic powder is used, the hemostatic time is increased and the sample amount is increased.

[0064] No hydroxypropyl-β-cyclodextrin was added to Comparative Example 2, and the absorbable hemostatic powder was modified potato starch microspheres. The water absorption rate and viscosity of the absorbable hemostatic powder prepared in Comparative Example 2 decreased when used, and the hemostatic time and sample usage increased, indicating that the hemostatic effect of the absorbable hemostatic powder prepared in Comparative Example 2 was inferior to that of Example 1. The addition of hydroxypropyl-β-cyclodextrin can effectively improve the water absorption and viscosity of the starch / cyclodextrin composite microspheres after absorbing water, so that the covering formed by the absorbable hemostatic powder absorbing blood has good viscosity and has a sealing effect on the wound, thereby shortening the hemostatic time and reducing the usage of the absorbable hemostatic powder, reducing the impact of the absorbable hemostatic powder on the human body after use. However, no hydroxypropyl-β-cyclodextrin was added to Comparative Example 2, which reduced the hemostatic effect of Comparative Example 2.

[0065] Compared with Example 1, the water absorption rate and viscosity of the absorbable hemostatic powder in Example 3-4 are reduced during use, and the hemostatic time and sample usage are increased, indicating that the hemostatic effect of the absorbable hemostatic powder prepared in Example 3-4 is inferior to that in Example 1. The modified potato starch used in Example 3-4 changes the mass ratio of maltotriase and α-amylase in the composite enzyme during enzymatic hydrolysis. There is a synergistic effect between maltotriase and α-amylase, and the mass ratio between the two directly affects the enzymatic hydrolysis effect of the composite enzyme on potato starch. When the mass ratio of the two changes, the enzymatic hydrolysis effect of the composite enzyme on potato starch becomes worse, the porosity of the surface of the enzymatically hydrolyzed potato starch decreases, the specific surface area decreases, and the water absorption rate decreases, thereby reducing the hemostatic effect of the absorbable hemostatic powder.

[0066] Compared with Example 1, the water absorption rate and viscosity of the absorbable hemostatic powder in Example 5-6 are reduced during use, and the hemostatic time and sample usage are increased, indicating that the hemostatic effect of the absorbable hemostatic powder prepared in Example 5-6 is inferior to that in Example 1. The modified potato starch used in Example 5-6 changes the amount of compound enzyme added during enzymatic hydrolysis. The amount of compound enzyme added directly affects the enzymatic hydrolysis of potato starch. Too high an amount added can easily cause excessive enzymatic hydrolysis of potato starch and disintegration, resulting in reduced water absorption. Too little an amount added can weaken the erosion of the potato starch surface and reduce the specific surface area, thereby reducing the hemostatic effect of the absorbable hemostatic powder.

[0067] Compared with Example 1, the water absorption rate and viscosity of the absorbable hemostatic powder in Example 7-8 are reduced when used, and the hemostatic time and sample usage are increased during hemostasis, indicating that the hemostatic effect of the absorbable hemostatic powder prepared in Example 7-8 is inferior to that of Example 1. The modified potato starch used in Example 7-8 is prepared by changing the mass ratio of deacetylated konjac glucomannan to enzymatically hydrolyzed potato starch. Deacetylated konjac glucomannan has good water absorption and can make the modified potato starch form a regular organizational structure, thereby improving the water absorption of the modified potato starch and the viscosity after water absorption, and at the same time enhancing the strength of the covering formed by the absorbable hemostatic powder after water absorption, thereby improving the hemostatic effect of the absorbable hemostatic powder.

[0068] Compared with Example 1, the water absorption rate and viscosity of the absorbable hemostatic powder in Example 9-10 are reduced when used, and the hemostatic time and sample usage are increased during hemostasis, indicating that the hemostatic effect of the absorbable hemostatic powder obtained in Example 9-10 is inferior to that in Example 1. The deacetylation degree of the deacetylated konjac glucomannan used in the preparation of the modified potato starch used in Example 9-10 is changed. The deacetylation degree of the deacetylated konjac glucomannan affects the water absorption of the modified potato starch, that is, the viscosity after water absorption. Too high or too low deacetylation will reduce the water absorption and viscosity of the modified potato starch, thereby reducing the hemostatic effect of the absorbable hemostatic powder.

[0069] Compared with Example 1, the water absorption rate and viscosity of the absorbable hemostatic powder in Example 11-12 are reduced during use, and the hemostatic time and sample usage are increased, indicating that the hemostatic effect of the absorbable hemostatic powder prepared in Example 11-12 is inferior to that in Example 1. Example 11-12 changes the mass ratio of modified potato starch to hydroxypropyl-β-cyclodextrin. The mass ratio of modified potato starch to hydroxypropyl-β-cyclodextrin directly affects the morphology and specific surface area of ​​starch / cyclodextrin composite microspheres. Changing the mass ratio of the two will make the morphology of starch / cyclodextrin composite microspheres irregular and reduce the specific surface area, thereby affecting the hemostatic effect of the absorbable hemostatic powder.

[0070] Compared with Example 1, the water absorption rate and viscosity of the absorbable hemostatic powder in Example 13-14 are increased when used, and the hemostatic time and sample usage are decreased, indicating that the hemostatic effect of the absorbable hemostatic powder prepared in Example 13-14 is better than that in Example 1. The hydroxypropyl-β-cyclodextrin used in Example 13-14 is modified with chitosan, which can effectively increase the specific surface area and water absorption of hydroxypropyl-β-cyclodextrin, thereby helping to increase the water absorption of starch / cyclodextrin composite microspheres, thereby improving the hemostatic effect of the absorbable hemostatic powder.

[0071] Compared with Example 1, the water absorption rate and viscosity of the absorbable hemostatic powder in Example 15-16 are increased during use, and the hemostatic time and sample usage are decreased, indicating that the hemostatic effect of the absorbable hemostatic powder prepared in Example 15-16 is better than that in Example 1. In Example 15-16, the starch / cyclodextrin composite microspheres are treated, and the outer side of the starch / cyclodextrin composite microspheres is coated with a layer of sodium alginate. Sodium alginate and calcium chloride are ion exchanged to obtain calcium alginate. Calcium alginate has the function of promoting red blood cell aggregation and accelerating the coagulation process, thereby further improving the hemostatic speed. At the same time, calcium alginate becomes gel-like after absorbing water, and has good water absorption and viscosity.

[0072] Compared with Example 15, the water absorption rate and viscosity of the absorbable hemostatic powder in Example 17 are reduced during use, and the hemostatic time and sample usage are increased, indicating that the hemostatic effect of the absorbable hemostatic powder prepared in Example 17 is inferior to that of Example 15, while the performance of the absorbable hemostatic powder prepared in Example 18 is similar to that of the absorbable hemostatic powder prepared in Example 15. Examples 17-18 change the mass ratio of calcium chloride and sodium alginate. When the amount of calcium chloride is reduced, the ion exchange between calcium ions and sodium alginate is incomplete, resulting in the generated calcium alginate having reduced viscosity, water absorption and coagulation function. When the amount of calcium chloride is increased, the degree of ion exchange is not significantly improved.

[0073] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A method for preparing absorbable hemostatic powder, characterized in that: The following steps are involved: S1: adding modified potato starch and hydroxypropyl-β-cyclodextrin into water and gelatinizing at 50-55°C to prepare a homogeneous solution; S2: adding a crosslinking agent to the homogeneous solution, mixing evenly, and then dropping it into liquid paraffin containing an emulsifier, and emulsifying at 55-60° C. for 30-40 minutes to obtain an emulsion; S3: Add sodium bisulfite to the emulsion, stir at 350-380 r / min for 2-3 hours, wash by centrifugation for multiple times, and freeze-dry to obtain starch / cyclodextrin composite microspheres, which are absorbable hemostatic powder.

2. The method for preparing an absorbable hemostatic powder according to claim 1, characterized in that: The mass ratio of the modified potato starch to hydroxypropyl-β-cyclodextrin is (2.13-2.54):(0.73-0.82).

3. The method for preparing an absorbable hemostatic powder according to claim 1, characterized in that: The preparation method of the modified potato starch comprises the following steps: dissolving potato starch in water, stirring the potato starch evenly with magnetic force to form a suspension, adding a composite enzyme, performing enzymolysis at 45-50° C. for 12 hours, adding a sodium hydroxide solution, centrifuging, and drying to obtain enzymolyzed potato starch; After dispersing enzymatically hydrolyzed potato starch in water to obtain a suspension, deacetylated konjac glucomannan is added, stirred and mixed evenly at 30-35° C., centrifuged, and dried to obtain modified potato starch.

4. The method for preparing an absorbable hemostatic powder according to claim 3, characterized in that: The complex enzyme comprises maltotriose enzyme and alpha-amylase in a mass ratio of (0.92-1.12):(6.81-7.21), and the added amount of the complex enzyme is 7.5-8.3wt% of the mass of potato starch.

5. The method for preparing an absorbable hemostatic powder according to claim 3, characterized in that: The mass ratio of the deacetylated konjac glucomannan to the enzymatically hydrolyzed potato starch is (0.83-0.91):(7.26-8.13).

6. The method for preparing an absorbable hemostatic powder according to claim 5, characterized in that: The deacetylation degree of the deacetylated konjac glucomannan is 45.62-51.91%.

7. The method for preparing an absorbable hemostatic powder according to claim 1, characterized in that: The hydroxypropyl-β-cyclodextrin is treated as follows: adding hydroxypropyl-β-cyclodextrin to a sodium carbonate solution, stirring until completely swollen, adding chitosan, stirring and refluxing at 85-90° C. for 2-2.5 hours, adjusting the pH to neutral, filtering, washing, and drying.

8. The method for preparing an absorbable hemostatic powder according to claim 1, characterized in that: The starch / cyclodextrin composite microspheres are further treated as follows: the starch / cyclodextrin composite microspheres are dispersed in a 2-4wt% sodium alginate solution, placed in a 55-60°C water bath, stirred for reaction for 3-4h, then calcium chloride solution is added dropwise, and after the addition is complete, the stirring reaction is continued for 20-30min, soaked for 4-5h, centrifuged, washed, and freeze-dried.

9. The method for preparing an absorbable hemostatic powder according to claim 8, characterized in that: The mass ratio of calcium chloride to sodium alginate is (0.85-0.96):(0.91-1.02).

10. An absorbable hemostatic powder, characterized in that: The absorbable hemostatic powder is prepared according to the preparation method of any one of claims 1 to 9.